Identification of Colletotrichum Species Associated with Blueberry Anthracnose in Sichuan, China - Liu, Xuan (Pathogens, 2020)
Anthracnose caused by Colletotrichum spp. is an important disease of blueberries and results in large economic losses for blueberry growers. Samples of anthracnose were collected from six main blueberry cultivation areas in Sichuan Province. In total, 74 Colletotrichum isolates were obtained through a single-spore purification method and identified to the species through morphological characteristics and phylogenetic analyses based on partial DNA sequences of glyceraldehyde-3-phosphate dehydrogenase (GAPDH), internal transcribed spacer (ITS) regions, and the β-tubulin (TUB2), actin (ACT) and calmodulin (CAL) genes. Among all species, Colletotrichum fructicola was the most dominant species, with an isolation percentage of up to 66.2% in Sichuan, followed by Colletotrichum siamense (17.6%), C. kahawae (5.4%), C. karstii (5.4%), C. nymphaeae (2.7%) and C. sichuaninese (2.7%). Pathogenicity tests showed all species were able to cause typical anthracnose symptoms on blueberry leaves and stems. Colletotrichum fructicola was the predominant species with strong aggressiveness. Moreover, C. fructicola, C. kahawae, C. sichuaninese and C. nymphaeae are first reported here to cause blueberry anthracnose. This study provides a comprehensive reference for the association of different Colletotrichum spp., which may support the sustainable management of blueberry anthracnose.